Genetic influence on circulating vitamin D among Saudi Arabians - Sadat-Ali, Mir (Saudi Med J, 2016)
OBJECTIVES: To examine the effect of most common studied single nucleotide polymorphisms (SNP) on serum 25-hydroxyvitamin D (25OHD) levels in Saudi Arabian population. METHOD: A cross-sectional observational study was carried out between July 2014 and October 2015, at King Fahd Hospital of the University (KFHU), Al-Khobar, Kingdom of Saudi Arabia. After informed consent, blood samples from 283 subjects living in the Eastern province were collected for 25-OHD measurement and genetic analysis of SNPs in vitamin D receptor (VDR) [rs2228570 and rs1544410], Cytochrome, P450 family 2 (CYP2R1) [rs10741657 and rs1993116], and Group-specific components (GC) [rs2282679 and rs4588]. RESULTS: Vitamin D deficiency was found in 87.6% and insufficiency in 7.7%. The percentages of the different alleles of the 6 SNPs tested ranged between 0-62.5%. There was significant difference between the AA, AG, and GG alleles of VDR rs2228570. The carries of GG allele was associated with increased risks of vitamin D insufficiency (p<0.002) and deficiency (p≤0.005). The CYP2R1 rs10741657 gene showed that AG and GG allele carriers had significant risk of vitamin D deficiency. AG allele (normal versus Insufficiency p<0.02 and normal versus deficiency p<0.08) and GG allele normal versus deficiency (p<0.002) and insufficiency versus deficiency (p<0.001). For group-specific components (GC rs4588), there was only significant difference between the normal and deficiency for the AC allele (p<0.0001). CONCLUSION: The presence of GG allele of the SNP rs2228570 of VDR gene, SNPs rs4588 of GC gene and CYP2R1 rs10741657 gene was associated with vitamin D deficiency.